Faktor-Faktor yang Mempengaruhi Financial Distress pada Perusahaan Transportasi di Indonesia dengan Firm Size sebagai Variabel Moderasi - Nadia Fathurrahmi Lawita; Intan Diane Binangkit (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2022)
This study was conducted to determine the effect of liquidity, leverage, profitability, and operating capacity on financial distress with firm size as the moderating variable. The research population includes transportation companies listed on the Indonesia Stock Exchange for the period 2018-2021 and a sample of 38 companies is obtained. The method used in this research is purposive sampling method. The results of the analysis are that the liquidity and leverage variables have a negative and insignificant effect on financial distress, the profitability and operating capacity variables have a positive and significant effect on financial distress, while the firm size variable is unable to moderate the effect of liquidity on financial distress, firm size is unable to moderate the leverage effect on financial distress. financial distress, firm size is not able to moderate the effect of profitability on financial distress.